Monetary policy as a tool of efficient management of the economy (ҚазҰУ хабаршысы. Экономика сериясы, 2019)
Monetary policy is one of the most powerful instruments of economic policy owned by thestate. This is a set of measures aimed at changing the money supply, loan amount, interest rate and regulationof the banking system as a whole. That is why the article discusses the main issues of monetarypolicy and its development trends. In other words, what methods and tools are currently used by theNational Bank of the Republic of Kazakhstan, their main advantages and disadvantages, macroeconomicresults of monetary policy. In this regard, the purpose of this article is to study the financial and creditmethods of state regulation of the economy of the Republic of Kazakhstan and the concept of monetarypolicy. The study used economic methods used in the study of economic conditions. The article analyzesthe situation and indicators of monetary policy for the last two years of 2017 and 2018, as wellas changes and trends in monetary policy in 2019. In 2018, the National Bank focused on the furtherdevelopment of the money and foreign exchange market, as well as the government securities market,and demonstrated the importance of a number of initiatives aimed at improving the effectiveness ofmonetary policy. The results of the study allow students to apply them during their studies.